(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Human Enhancement is a modification aimed at improving individual human performance through scientific or technological interventions in the human body. Sure enough, it is based on techniques aimed to improve the knowledge, to change the physique appearance, to increase the physique and the athletic performance, to intensify the working capabilities. The Authors propose to identify the ethical and juridical frames, as well as the medical legal and medical social ones, in which to assimilate the enhancement, duly considering that it’s inevitable, since human beings are naturally competitive and since the change is constant and it’s the historical main character of every social and cultural revolution, in other words it’s the main reason of our evolution. Therefore, we need to value if the application of the enhancement technologies is harmful of the human dignity or if it’s an useful tool to improve the human life’s condition and then his own dignity.